Quality of life in Cushing's syndrome. Issue 1 (January 2021) - Bride, Margot Mc; Crespo, Iris; Webb, Susan M.; Valassi, Elena
Abstract : Measurement of Health-Related Quality of Life (HRQoL) is emerging as an important clinical endpoint which complements diagnostic workup and contributes to place patients at the centre of the decision-making process through the recognition of their needs, concerns, goals and expectations. Chronic excessive cortisol exposure in Cushing's syndrome (CS) causes severe physical and psychological morbidity which invariably affects HRQoL during the active phase of the disease and even after successful treatment. This sustained deterioration of patient's wellbeing is partly related to the persistence of several features associated with prior cortisol excess, including affective disorders, cognitive dysfunctions and negative illness perception. The aim of this review is to summarize the most recent evidence on HRQoL in CS, including the main determinants of its impairment and the results of some educational programs specifically addressed to improve patient's coping abilities. The preliminary results of an unpublished survey on patient's unmet needs will also be presented.